An Analytical Investigation of Consumer Buying Perception towards packaged vegetables and fruits - Poonam Singh, Abhinav Yadav, Shanti Swaroop Chauhan, Pradhyuman Singh Lakhawat, (European Economic Letters (EEL), 2023)
The size of the global market for fresh food packaging was estimated at USD 123.4 billion in 2020, and it is anticipated to increase at a CAGR of 5.0% from 2021 to 2028. Over the course of the forecast period, diet- and health-conscious customers are anticipated to drive growth in demand for organic fresh food goods such fruits, vegetables, and dairy. Additionally, to appeal to a consumer base in the area who is concerned about the environment, a rising number of foodservice operators and retail chains in different economies are predicted to move from plastic packaging to a sustainable alternative. Thus, it is anticipated that the aforementioned causes will increase demand for eco-friendly fresh food packaging. Sales of minimally packaged vegetables and fruits are rapidly increasing since many agencies, organizations and celebrities are engaged to create their awareness in terms of convenience and healthiness. Present study trying to investigate the consumer buying perception towards these packaged fruits and vegetables. The buying perception has been investigated through implementing a consumer survey in Prayagraj City of Uttar Pradesh State of India. The ﬁrst part of the survey tool consisted of demographic profiles of respondents (n=385). The second part of the survey tool was administered to randomly selected consumers (n=385). The likelihood of buying minimally packaged vegetables and fruits tends to be higher among city residing educated consumers in compare to consumers with rural background. Search attributes emerge in terms of importance during the purchasing stage, while experience attributes gain importance after consuming the packaged vegetables and fruits. The most important motivation for purchasing packaged vegetables and fruits relates to convenience and speed, especially for consumers who buy this product during weekends. Although health and nutritional value scored relatively low in terms of importance during the purchasing and consumption stages of packaged vegetables and fruits, many of the studies revealed that consumers with a high awareness of the health are less attached with packaged vegetables and fruits in compare to fresh one.